HVAC electricity and natural gas saving potential of a novel switchable window compared to conventional glazing systems: A Canadian house case study in city of Toronto. (1st January 2022) - Sadooghi, Parham
Highlights: A switchable glazing system is proposed to improve building energy performance. Energy saving potential of the system is compared with conventional glazing systems. Hourly strategies are developed to improve performance of integrated coatings. WWR and SHGC effect on building electricity and natural gas consumption are analyzed. Switchable glazing system reduces energy bill by 47% compared to single pane window. Abstract: This paper investigates performance of a novel switchable window to reduce HVAC energy consumption of a typical Canadian house located in city of Toronto. Energy saving potential of the proposed glazing system is compared with highly efficient low emissivity coated double and triple pane static windows with low, medium, and high solar heat gain coefficients. Glazing systems material properties are chosen from LBNL experimentally validated international glazing system data base, (IGDB). EnergyPlus software is used to simulate and predict heating and cooling loads of the house with natural gas furnace and electric coils as the building HVAC system. Considering windows orientation, two operation strategies are developed to enhance performance of the switchable window inter-pane coatings and adjust desired solar heat gain and thermal resistance in winter and summer. Medium and high window to wall ratio effects on glazing systems performance are investigated and the result shows that proposed system significantly reduce building heating and cooling energy consumption. Considering window to wall ratio of 90%, compared to conventional clear single and double pane windows, energy analysis shows that switchable glazing system decreases HVAC annual energy bill by 47% and 33%, respectively.